Tick bite inflammatory alopecia. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
The skin lesions caused directly by the tick bite are related to the persistence time of the tick on the scalp and individual reactivity. The lesions range from poorly visible findings to erythema followed by scaling, exudative lesions up to suppuration, chronic granulomatous lesions that can simulate lymphoma or indeterminate cells histiocytosis (2), cutaneous necrosis with formation of deep mold ulcers. Many of these lesions are associated with generally transient alopecia (1). This differs from inflammatory alopecia due to other causes because in the history there is almost always the presence of the tick and the absence of other responsible factors. Physical examination and dermoscopy rule out the diagnosis of alopecia areata due to the absence of exclamation marks and other typical signs. The presence of adenopathy is frequent.